[tex]\frac{5}{6}\left(x-\frac{10}{3}\cdot \frac{6}{5}\right)=\frac{11}{4}+\frac{\frac{15}{4}}{\frac{5}{3}}[/tex]
[tex]\frac{5}{6}\left(x-\frac{10}{3}\cdot \frac{6}{5}\right)=\frac{11}{4}+\frac{9}{4}[/tex]
[tex]\frac{5}{6}\left(x-\frac{10}{3}\cdot \frac{6}{5}\right)=\frac{11+9}{4}[/tex]
[tex]\frac{5}{6}\left(x-\frac{10}{3}\cdot \frac{6}{5}\right)=\frac{20}{4}[/tex]
[tex]\frac{5}{6}\left(x-\frac{10}{3}\cdot \frac{6}{5}\right)=5[/tex]
[tex]5\left(x-4\right)=30[/tex]
[tex]x-4=\frac{30}{5}[/tex]
[tex]x-4=6[/tex]
[tex]x=6+4[/tex]
[tex]x=10[/tex]